The Mission of History Education in Forming Future - Ciydem, Erol (Elsevier BV, 2012)
AbstractDevelopments observed on the base of global phase and reconstructed scientific paradigm has created a chaotic atmosphere as well as it has had an effect on living conditions of both social beings and individuals. Interest to history has increased as a result of conditions related with struggle to handle with these hardships. However history in the past was hardly able to comprehend and dealt with this interest. Therefore a new approach to history inevitably emerged. In this regard it is required to create a new approach to history with its subject; human being. As of the relationship between developments and positioning human beings, the mission of the history education in terms of forming present and future is questioned. Unfortunately this case hasn’t been adequately examined yet. Based on this case it is aimed to emphasize what is the mission of the history education in terms of forming future, what for it and how is it utilized to fulfill this task? To accomplish the task literature and available equipment will be analytically reviewed.
Keywords: History; Globalization; Education; 4. Education